Characterization of reproductive health in dogs - Sánchez Riquelme, Alfonso (2019)
Considering reproductive health as an important component of animal welfare in dogs, the purpose of this study was to characterize and compare some reproductive health parameters in 30 intact English Bulldog, clinically healthy, distributed in two age groups: A, 1-4 years (n = 15) and B: ≥5 years (n = 15). The evaluation was carried out through a reproductive physical examination and testicular and prostate ultrasonographic examination. The average age of groups A and B was 2.19 ± 1.08 years and 7.31 ± 3.12 years, respectively. In total, 16.6% of the specimens presented urethral prolapse without differences by age group. The frequencies of asymmetry and testicular flaccidity were 0.06 in both groups. The ultrasonographic evaluation showed a higher frequency of alterations of the testicular parenchyma, especially heterogeneity and presence of anechoic foci in Group B (0.4) than in Group A (0.06) (p<0.05). In prostate, high frequency of ecotexture anomalies was observed (0.8) and presence of anechoic foci (0.66) in group B with respect to 0.13 and 0.66 group A, respectively (p<0.05). The prostate diameter had values ​​of 3.06 ± 0.45 cm and 4.27 ± 0.37 cm in groups A and B, respectively (p<0.05). It should be noted that prostatomegaly was observed in 80% of the specimens ≥5 years and only in 20% of the younger dogs (p <0.05).